Service Quality Research to Increase Customer Satisfaction at Yamaha 71 Motor Pamulang Workshop - Bayu Lhutfi R; Erika; Iqbal Dzulfukor (Jurnal Ekonomi dan Bisnis Digital, 2022)
The purpose of this research is to analyze the quality of service to increase customer satisfaction at the automotive repair shop "Yamaha Workshop 71 Pamulang". The method of this study uses a quantitative descriptive method, which is a form of research based on data collected during systematic research regarding the facts and properties of the object studied by combining those involved in it, then interpreted based on theories and literature related to quality. service. The results showed that so far, namely in terms of reliability, from the TCR results it was found that: the speed of service provided by employees showed 102 people were satisfied, Assurance, from the TCR results it was found that: the ability of employees to carry out their duties, politeness, hospitality or employee behavior when serving customers, creating a sense of customer security when paying transactions with the highest amount being 102 in the satisfied category, physical evidence (Tangibles) from the TCR results obtained. as many as 11 people were dissatisfied with the physical evidence provided by the Yamaha 71 Pamulang Workshop.